2022
DOI: 10.1155/2022/1724906
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Potential of Streptomyces spp. Isolated from the Rift Valley Regions of Ethiopia

Abstract: The study was undertaken to isolate, screen, and identify actinomycetes with antimicrobial metabolites. Twenty-one composite soil samples were randomly collected from various unique agroecological niches in the Rift Valley of Ethiopia. The soil samples were serially diluted and spread on starch casein agar medium supplemented with 50 μg/ml cycloheximide and 25 μg/ml nalidixic acid. Two hundred and forty-nine (249) actinomycetes cultures were isolated and screened by cross streaking against various human pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…RVE002. 25 Analysis of the GC-MS results showed that the NIST database contained six antimicrobial compounds from the extract. Six compounds were identified in the extracts of Streptomyces sp.…”
Section: Streptomyces Have Been Exploredmentioning
confidence: 99%
“…RVE002. 25 Analysis of the GC-MS results showed that the NIST database contained six antimicrobial compounds from the extract. Six compounds were identified in the extracts of Streptomyces sp.…”
Section: Streptomyces Have Been Exploredmentioning
confidence: 99%
“…Streptomyces are gram-positive, filamentous bacteria that form extensively branched substrate mycelium. It is also the ability to produce antibiotics or other industrially valuable secondary metabolites (Kumar et al 2007 ; Elias et al 2022 ) and some of the genus members are used as biocontrol agents against plant disease (Simizu et al 2009 ). Some S treptomyces species can also cause a plant disease called scab, which is an important problem for potato growers worldwide (Bukhalid and Loria 1997 ) and the disease significantly reduces the quality of tubers (Gutierrez et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%